Evaluation of Human Anatomy and Physiology Concept Mastery Among Midwifery Students - Fony, Fony; Alam, Hardianti H.P; Sukmawati, Sukmawati; Senolangi, Trinarti (Universitas Negeri Makassar, 2025)
Abstract. This study aims to evaluate the level of midwifery students’ mastery of human anatomy and physiology concepts as part of the core curriculum in health education. Anatomy and physiology serve as fundamental pillars in midwifery practice, as they are directly related to understanding the processes of pregnancy, childbirth, and the postpartum period. This research employed a descriptive quantitative approach through a survey involving 50 second- and fourth-semester students. The results showed that second-semester students had a higher level of mastery (77.75%) compared to fourth-semester students (68%). Furthermore, male students demonstrated a higher level of understanding (81.25%) than female students (74.52%). These differences may be influenced by learning styles, motivation, and academic experience. The collected data were analyzed using descriptive statistical methods, including mean and percentage calculations, to compare levels of conceptual understanding across student groups. The findings provide important implications for developing more adaptive learning strategies in anatomy and physiology courses within midwifery programs.Keywords: anatomy, concept mastery, human physiology, midwifery, students